A gene adjacent to satellite DNA in Drosophila melanogaster. - Carlson, M (1978)
Several copies of a sequence adjacent to 1.688 g/cm3 satellite DNA in the Drosophila melanogaster genome have been isolated by molecular cloning. This sequence, called the Dm142 gene, is homologous to a 1.6-kilobase RNA found in both D. melanogaster embryos and tissue culture cells. One cloned DNA segment includes two copies of the Dm142 gene and 1.688 g/cm3 satellite DNA sequences, which are located between and flanking both gene copies. The Dm142 gene is repeated many times in the D. melanogaster genome, and some copies are not flanked by 1,688 g/cm3 satellite DNA.